2020
DOI: 10.1038/s41375-020-0743-y
|View full text |Cite|
|
Sign up to set email alerts
|

Single-agent activity of phosphatidylinositol 3-kinase inhibition with copanlisib in patients with molecularly defined relapsed or refractory diffuse large B-cell lymphoma

Abstract: Patients with relapsed/refractory diffuse large B-cell lymphoma (DLBCL) have adverse outcomes. We evaluated the efficacy and safety of the phosphatidylinositol 3-kinase inhibitor copanlisib in patients with relapsed/refractory DLBCL and assessed the relationship between efficacy and DLBCL cell of origin (COO; activated B-cell like [ABC] and germinal center B-cell like [GCB]) and other biomarkers. The primary endpoint was objective response rate (ORR) in DLBCL COO subgroups (ABC, GCB, and unclassifiable) and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…The efficacy data reported herein are consistent with the findings of a phase 2 study of the pan-PI3K inhibitor, copanlisib (with preferential activity against the a and d isoforms), conducted in patients with relapsed or refractory DLBCL [22]. The ORR reported herein is 25.5% (N ¼ 55); the ORRs observed with copanlisib in the full cohort and per-protocol analysis sets were 19.4% (N ¼ 67) and 25.0% (N ¼ 40), respectively.…”
Section: Discussionsupporting
confidence: 85%
“…The efficacy data reported herein are consistent with the findings of a phase 2 study of the pan-PI3K inhibitor, copanlisib (with preferential activity against the a and d isoforms), conducted in patients with relapsed or refractory DLBCL [22]. The ORR reported herein is 25.5% (N ¼ 55); the ORRs observed with copanlisib in the full cohort and per-protocol analysis sets were 19.4% (N ¼ 67) and 25.0% (N ¼ 40), respectively.…”
Section: Discussionsupporting
confidence: 85%
“…[35][36][37]42 In studies with pan-PI3K inhibitors in patients with DLBCL (buparlisib, voxtalisib, copanlisib), reported ORR ranged from 5% to 19% (CR 0-7%), with median DOR of 2.2 months to 4.3 months and median PFS from 1.8 months to 7.1 months. 40,41,43 In studies with pan-PI3K inhibitors reporting outcomes in patients with MCL (buparlisib, voxtalisib), ORR J o u r n a l P r e -p r o o f ranged from 12% to 23% (CR 5-7%), and median PFS ranged from 2.0 months to 11.3 months. 40,41 There are currently no published manuscripts or ongoing clinical trials of duvelisib in aggressive B-cell NHL.…”
Section: Overview Of Efficacy With Pi3k Inhibitors In Developmentmentioning
confidence: 99%
“…These features are sometimes cell type specific and may account in part for the different activity of the various BCR inhibitors in different B cell malignancies. For example, in addition to PI3Kδ, the related kinase PI3Kα has been implicated in signaling through the BCR in Activated B cell-like (ABC) DLBCL [ 16 , 17 ], providing a potential explanation for the greater clinical activity of the dual PI3Kα/δ inhibitor copanlisib compared to the PI3Kδ inhibitor idelalisib in patients with DLBCL [ 18 , 19 ]. Similarly, a recent study from our group showed that two pathways downstream of the BCR are involved in inactivation of the kinase GSK3 in chronic lymphocytic leukemia (CLL) cells, resulting in a different capacity of SYK, BTK, and PI3Kδ inhibitors to reduce the expression of the antiapoptotic protein Mcl-1, which is negatively regulated by GSK3 [ 20 ].…”
Section: Bcr Signaling In Normal and Malignant B Cellsmentioning
confidence: 99%
“…Copanlisib has also shown promising results in phase 2 trials of patients with R/R lymphoma, resulting in ORRs of 75% in SLL, of 59% in FL, of 70% in MZL, and of 64% in MCL [ 195 , 211 ]. More recently, copanlisib was tested in a phase 2 trial of patients with relapsed/refractory DLBCL, demonstrating ORRs of 31.6% and 13.3% in ABC and GCB DLBCL patients, respectively [ 19 ].…”
Section: Bcr Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation